Assessment of knowledge on child sexual abuse among school going adolescent girls (age 14-17 years) in urban slums of Kakinada, Andhra Pradesh: - Garapati, Sridevi; Peetala, Sujatha; Goru, Krishna B. (International Journal Of Community Medicine And Public Health, 2024)
Background: Child sexual abuse (CSA) is a hidden, psychologically complex, and socially sensitive issue. The Protection of Children from Sexual Offences (POCSO) Act, 2012 defines different forms of sexual abuse. Child sexual abuse can result in both short-term and long-term consequences including physical, mental, and behavioural among victims. It is very important to understand and improve public awareness of sexual abuse prevention. Objectives were to study the awareness on child sexual abuse among adolescent girls between 14 to 17 years of age and to identify the socio-demographic factors related to their awareness on child sexual abuse. Methods: A cross-sectional study was conducted among adolescent girls in 3 urban slums in Kakinada, Andhra Pradesh during September to November 2019 using a semi-structured questionnaire. A total of 343 children participated in the study. Data analysis was done with statistical package for the social sciences (SPSS) version 16. Results: Mean age of the study population was15.82±1.08 years. Half (53.9%) of them belong to BC, 73.8% Hindu, 87.4% of the participants have parents and 70.6% belong to nuclear family. Overall knowledge on child sexual abuse was 60.3%, majority (67.1%) do not know where sexual abuse can take place. Knowledge on getting physical, mental, and behavioural problems due to abuse was 72.0%, 69.1% and 46.1% respectively and none of them were aware of POCSO act. Conclusions: Knowledge gaps and misperceptions about child sexual abuse are widespread. Children, Parents, caregivers, professionals in health and education and law enforcement should be prime targets for awareness-building and empathy-building for disclosure and appropriate response.